Dampak perkembangan teknologi informasi pengendalian fraud bidang akuntansi - Faadihilah, Illona (Maliki Interdisciplinary Journal, 2024)
The era of globalisation has brought many developments in various fields of life, especially in the field of information technology. The rapid development of information technology has brought many positive and negative impacts on life. One of the fields that has the most positive and negative impact with the development of this technology is the economy. Information technology is developing rapidly in the economic sector, especially related to finance and fraud control that occurs in a company or MSME. The purpose of this study is to determine the impact of information technology developments in controlling fraud in the field of accounting (recording). The impact of the development of information technology has had many positive impacts or even negative impacts on the company’s financial sector. Data retrieval techniques using literature study methods conducted via online and offline. In this research activity, the results obtained show that the development of information technology has brought many positive impacts to control fraud on corporate financial accounting records. In addition to the positive impact, there is also a negative impact on corporate accounting records.